Meningkatkan Hasil Belajar Matematika Melalui Model Kooperatif Tipe Giving Question and Getting Answer Siswa SMP Negeri 3 Palibelo - Rizcky Juliawan (Departement of Mathematics Education, 2023)
The main problem in education in Indonesia is the low learning outcomes of students in schools. This happened at SMP Negeri 3 Palibelo. So far, mathematics learning in schools is still focused on teachers and teachers do not provide opportunities for students to construct mathematical concepts / principles according to ability through interaction between students. In learning activities, the emphasis of this aspect can be applied by cooperative learning of the type of giving questions and getting answers. This study aims to describe the results of learning mathematics through a cooperative model of giving questions and getting answers. The type of research carried out is Classroom Action Research with research instruments using learning outcome tests and observation sheets for student learning activities every cycle. The results obtained were in the form of qualitative data that showed an increase in learning activities in the first cycle, the average student learning activity score of 2.8 and an increase in cycle II of 3.8, an increase in learning outcomes in cycle I the average student score of 65.22 increased to 86.96 in cycle II as well as classical completeness in cycle I reached 65.22% increased to 86.96% in cycle II. From the results of this study, it can be concluded that the application of a cooperative model of giving questions and getting answers can improve student mathematics learning outcomes